The EM4 Addition Affect Water Absorption Time and Compost Quality in Biopore Infiltration Hole - Putri, Marsha Savira Agatha; Sulistiono, Eko; Prasidya , Denaya Andrya; Ni'am, Achmad Chusnun; Affandy, Nur Azizah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
A biopore infiltration hole can handle organic household waste for the composting process. It can be optimized by adding an Effective Microorganism 4 (EM4) activator. This study aims to determine the effect of EM4 addition on water adsorption time, compost weight, and compost quality, according to SNI 19-7030-2004. Lamongan Islamic University's Laboratory of Environmental and Health Science determined the compost test's nutrient content. A cylindrical hole was drilled into the ground using a BIH drill with a diameter of 10 cm and a depth of 50, 75, and 100 cm, with a distance of 100 cm for each hole. The materials used in this study included domestic organic waste, leaves explicitly, and kitchen waste, a 50-ml liquid EM4 "Agriculture" activator diluted with 100 ml of distilled water, and 10 grams of granulated sugar.  The experiment was conducted for 15, 30, and 45 days. To measure the water absorption time, a 2x1x1 m barrier is needed to accommodate 2 m3. The difference in BIH diameter can affect the infiltration rate at the Biopores Infiltration Hole (BIH). The measurement's highest water absorption occurred at the beginning of the 15th day. The addition of EM4 affects the decomposition process and can increase the water absorption rate for 45 days. The EM4 additions affect the decomposition process's timing. Additionally, the addition of EM4 impacts the nutrients in the compost. The addition of EM4 increased the value of C-organic, nitrogen, phosphorus, and total potassium in the BIH compost.